POLA PENDIDIKAN DAN POLA DAKWAH ISLAMIC CENTRE MU’ADZ BIN JABAL (ICM) DI KOTA KENDARI - Asliah Zainal (Institut Agama Islam Negeri Kendari, 2017)
Modernization and globalization in the world is characterized by the proliferation of modern religious institutions that attract people. This study attempts to analyze one institution namely Islamic Center Mu’adz bin Jabal (ICM) in Kendari, Southeast Sulawesi. This study indicates that regarded as the Muslim community center with initiation to embrace all groups of society, the program of ICM focuses on education, dakwah, social activities, and other community services. The education curriculum of this institution is using decentralized curriculum called thafidz Al-Quran, the development of infrastructures, and educational programs for kindergarten, elementary school, junior and senior high school. Meanwhile, the pattern of dakwah conducted by ICM is to provide adequate Islamic material, pengajian accessibility targeting every level of community as well as to use social media such as radio, ebsite, and facebook to do dakwah. With the pattern of education and dakwah are offered, ICM receives signifficantly positive response and interest from communities around, also strengthened by the progression of infrastructure development which is relatively faster compared to other educational institutions in Kendari. Moreover, this study confirms that the spirituality of urban society in Kendari obtains the suitable locus because Islamic Centre Mu’adz bin Jabal as the alternative solution to fulfill the religious need of society for any ideology.